Knowledge Management of the Mango Export Enterprise of Bang Khla District, Chachoengsao Province - สินทรโก, อธิภัทร; Chaiyarit, Atiyaphorn; Khunkha, Nopporn (NKRAFA Journal of Humanities and Social Sciences, 2020)
This research was conducted to study the knowledge management of the mango export enterprise of Bang Khla District, Chachoengsao Province. The objectives of this research aimed to study the knowledge of local wisdom on mango production, knowledge management process of mango production and conditions affecting success on mango production of the mango export enterprise of Bang Khla District, Chachoengsao Province. This research was a qualitative research. Data were collected by an in-depth interview. Instrument used for this research was a semi-structured interview. There were 15 key informants. The findings revealed that the knowledge of mango production was a hereditary knowledge of the producing process from former generations who had pioneered the mango orchard. It consisted of propagation, maintenance, harvest, and quality control of transportation. Moreover, the surrounding geographical condition still played a pivotal role in increasing product quality as well as outstanding size and taste of mango products. For knowledge management process of the mango export enterprise, it consisted of knowledge identification, knowledge creation and acquisition, knowledge access, knowledge sharing, and knowledge learning. However, the knowledge organization and the knowledge codification and refinement had not been systematically conducted. For conditions affecting the success of mango production of the mango export enterprise, it was comprised of five factors:1) geographical condition, 2) leaders, 3) product quality, 4) member relationship, and 5) continuous product development.